Analisis Fanatisme Online TEUME di Akun Twitter @TREASURE_INA - Djayani, Alya; Hepy Prasilia; Naura Rainsyifa Nandra (Program Studi Ilmu Komunikasi Fakultas Ilmu Komunikasi Universitas Sumatera Selatan, 2025)
ABSTRACT Treasure as one of the Korean boy bands that has fanatical fans. Fans from various countries who have become fangirls and fanboys as female and male fans who are fans of their idols will not be separated from social interactions among fans who idolize a group. The form of interactivity of a group of boy band and girl band kpop fans nowadays does not only occur directly but many occur virtually by using social media such as twitter as a medium or tool for exchanging news, videos, photos, and even the schedule of a group's activities. Female fans (fangirls) in a (fandom), which is a term for a collection of people from various countries who support a group, one of which is Teume who idolizes Treasure, has created a fangirling culture seen from their interactivity and productivity in sending messages on Twitter. This study aims to analyze the ineractivity of fans from various countries in using Twitter to produce virtual values of fangirling culture which includes expressions and interactions that occur with fellow fans using virtual ethnographic research methods. This research shows the success of South Korea in shaping a fangirling culture that includes aspects of fan interaction, art, and works on Twitter as a manifestation of the success of K-Pop music in influencing a person's fanaticism towards popular culture from Korea.